2005
DOI: 10.1038/sj.onc.1208373
|View full text |Cite
|
Sign up to set email alerts
|

Coactivation of nuclear receptors and myogenic factors induces the major BTG1 influence on muscle differentiation

Abstract: The btg1 (B-cell translocation gene 1) gene coding sequence was isolated from a translocation break point in a case of B-cell chronic lymphocytic leukaemia. We have already shown that BTG1, considered as an antiproliferative protein, strongly stimulates myoblast differentiation. However, the mechanisms involved in this influence remained unknown. In cultured myoblasts, we found that BTG1 stimulates the transcriptional activity of nuclear receptors (T3 and all-trans retinoic acid receptors but not RXRa and PPAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 45 publications
4
56
0
Order By: Relevance
“…The role of Btg1 gene in myoblast differentiation is well documented by in vitro studies, and seems to rely on its ability to interact with and stimulate the activity of several myogenic factors, including the bHLH transcription factor MyoD (Marchal et al, 1995;Rodier et al, 1999;Busson et al, 2005). Our results reveal a high expression of Btg1 in the myotome, further suggesting its involvement in the regulation of myoblast differentiation in vivo.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The role of Btg1 gene in myoblast differentiation is well documented by in vitro studies, and seems to rely on its ability to interact with and stimulate the activity of several myogenic factors, including the bHLH transcription factor MyoD (Marchal et al, 1995;Rodier et al, 1999;Busson et al, 2005). Our results reveal a high expression of Btg1 in the myotome, further suggesting its involvement in the regulation of myoblast differentiation in vivo.…”
Section: Discussionsupporting
confidence: 68%
“…For example, it has been found that Btg2 impairs G1-S cell cyclephase progression by inhibiting cyclin D1 transcription (Guardavaccaro et al, 2000), that it can associate with HoxB9 (Prevot et al, 2000), and BMPregulated Smad1 and 8 (Park et al, 2004) to promote their transcriptional activity, and that it can enhance Math1 promoter activity (Canzoniere et al, 2004). Similarly, Btg1 has been shown to interact with and stimulate the activity of transcription factors that positively regulate myogenic processes, in particular myogenic factors such as MyoD, all-trans retinoic acid receptors, and the T3 receptor TR␣1 (Busson et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NCoR complex regulates genes important for muscle differentiation, including MyoD, Myf5 and myogenin (96), suggesting a specific pathway by which emerin might influence muscle differentiation. We therefore propose that emerin may regulate chromatin dynamics, at least in part, by associating with the NCoR complex in vivo, and that loss of this interaction may contribute to EDMD disease.…”
Section: Validation Of Emerin-associated Ncor Complex Components In Vivomentioning
confidence: 99%
“…7,8) Intriguingly, the conserved BTG/Tob domain is implicated as a region that allows for interaction with a variety of transcription factors, suggesting that BTG/Tob contributes to the regulation of DNA-binding of sequence-specific transcription factors. [9][10][11] BTG/Tob family members also interact with subunit 7 of the chemokine (C-C motif) receptor 4 (CCR4)-negative regulator of transcription (NOT) complex (CNOT7) or CNOT8 6,[12][13][14] ; the CCR4-NOT complex regulates transcription and mRNA turnover. 15,16) Furthermore, it was reported that BTG2 and Tob participate in mRNA turnover by promoting mRNA deadenylating activity of the CCR4-NOT complex.…”
mentioning
confidence: 99%